2012
DOI: 10.1103/physrevb.85.224404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of half-metallic antiferromagnetism inA2CrFeO6(A<

Abstract: The nearly well-ordered double perovskite La2CrFeO6 has been synthesized recently. Contrary to previous theoretical predictions, but in agreement with experimental observations, our first principle calculations indicate an insulating ferrimagnet La2CrFeO6 with antialigned S= Fe 3+ ions, using the local spin density approximation (LSDA), a correlated band theory LDA+U, and a semilocal functional modified Becke-Johnson method. Additionally, we investigated the double perovskite Sr2CrFeO6, which is as yet unsynth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Double perovskite La 2 CrFeO 6 is an example of this class that has been synthesized using the pulsed laser deposition technique with a high degree of Cr and Fe ordering [34,35] and the elec-tronic properties of this compound have been studied by the first-principles calculations. [36] Unlike the randomly distributed Cr and Fe disordered AFM perovskite LaCr 0.5 Fe 0.5 O 3 , the ordered La 2 CrFeO 6 double perovskite demonstrated a ferrimagnetic (FiM) nature with a saturation magnetization of ∼ 2μ B per formula unit (f.u.). [34,35] Recently Majumder et al [3] reported a saturation magnetization of ∼ 0.8 μB f.u.…”
Section: Introductionmentioning
confidence: 97%
“…Double perovskite La 2 CrFeO 6 is an example of this class that has been synthesized using the pulsed laser deposition technique with a high degree of Cr and Fe ordering [34,35] and the elec-tronic properties of this compound have been studied by the first-principles calculations. [36] Unlike the randomly distributed Cr and Fe disordered AFM perovskite LaCr 0.5 Fe 0.5 O 3 , the ordered La 2 CrFeO 6 double perovskite demonstrated a ferrimagnetic (FiM) nature with a saturation magnetization of ∼ 2μ B per formula unit (f.u.). [34,35] Recently Majumder et al [3] reported a saturation magnetization of ∼ 0.8 μB f.u.…”
Section: Introductionmentioning
confidence: 97%
“…Although CHMs have been proposed in diverse crystal structures, [2] perovskite-or Heusler-related systems have been regarded as the most promising candidates. [2,3,4,5,6,7] Recently, Felser and coworkers realized CHM in the Heusler Mn 3 Ga, in which a small band overlap was observed, [7] by substitution of some Mn ions with Pt ions. [8] Kurt et al also observed the CHM in Ru-doped Mn 2 Ga thin films.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Ref. [13], the CHM state may not be the ground state. In this section, the magnetic evaluation of Ba 2 PrVO 6 is studied by fixed spin moment (FSM) calculations within LSDA+U, and the results are shown in Figure 5.…”
Section: Magnetic Evaluation Of Ba 2 Prvomentioning
confidence: 96%
“…DP Ba 2 V T O 6 (T=Nb, Mo) [19] are not HM ferromagnets within local spin density approximation (LSDA), but HM ferromagnets under LSDA+U (considering the Coulomb correlations). DP La 2 CrF eO 6 is predicted to be a HM ferrimagnet by both experiment [20] and density function theory (DFT) calculations [13]. With LSDA calculations, Lee reported DP Sr 2 CrF eO 6 to be a simple metallic ferrimagnet in Ref.…”
Section: Introductionmentioning
confidence: 97%